(3eONd efgLj (B- (3GOGQjs - (3Ydj adGM(B, (3GdRYHjs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2010)
(3ebOeI aj efGgL h CSGdjH GdHMK GdYdej aj ejOGf GdJShjb , CfhGY GdHMhK GdYdejI , NWhGJ GdHMhK GdYdejI (B((3GdefgLjI GdYdejI(B) (3, LeY GdHjGfGJ aj GdHMhK GdYdejI ELQGA GdJUeje GdefgLj ddHMK GdYdej , COhGJ h efGgL GdHMK GdYdej, CfhGY GdYjfGJ aj GdHMhK GdYdejI , GdGSJHjGf COGI GdOQGSI aj GdHNK GdYdej , HjFI GdHMhK GdYdejI , fXe GdeYdheGJ GdJShjbjI , ESJNOGeGJ GdecJHI h CSGdjH GdJhKjb , JWHjbGJ YedjI ddHMhK GdJShjbjI GdYdejI (B.s
(3eQGLY U(B.421 (3; edGMb U(B.339 (3; eUWdMGJ U(B.417s
Keywords: (3COGQI GdeHjYGJs; (3CSGdjH GdHMKs; (3GdHMK GdYdejs; (3GdJShjbs